(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides an analytical overview of the transformation of women’s social and legal status in the 20th and early 21st centuries, with a special focus on the role of "beauty" in the process of gender equality. It explores how the concept of beauty has evolved historically, religiously, culturally, and economically, and how it has become institutionalized in patriarchal societies. The paper also analyzes how modern industry has commercialized female beauty and how beauty standards can impose restrictions on women’s freedom and agency. Additionally, statistical data is used to illustrate the decline in birth rates and the changing role of women in family and society.